Organization Of Monitoring The Quality Of Services Provided To Prevent And Combat Postpartum Bleeding In Women - Adilova Sojida Xurramovna; Jozilova Nigora Mamadaliyevna; Boltayev Anvar Ismayilovich; Sobirova Karomat Salimovna; Sindarov Ulugbek To’lqinovich; Ochilov Elyor Elmirzayevich; Raximqulova Zuxra Abdumannonovna; Jiyanova Zuxra Abduvaxobovna (Zien Journals, 2026)
This article describes how to monitor the quality of care for women during pregnancy and childbirth for postpartum haemorrhage, evaluate the clinical and cost-effectiveness of care, standard requirements, and conduct surveys, patient reviews and prioritize complaints and appeals. . feedback on patient satisfaction monitoring
Keywords: postpartum hemorrhage; observation; medical care; professional development